10-minute CBT : integrating cognitive-behavioral strategies into your practice - Otto, Michael W. (Oxford University Press, 2011)
This manual provides easy-to-use, accessible ways for clinicians to add targeted CBT elements into the ongoing practice of psychotherapy across a range of treatment orientations and practice settings.